Charactertization of poly (D, L-LACTIDE-CO-GLYCOLYDE) film for in vivo engineered biotube coating - Felix Fennardi (2014)
Cardiovascular disease remains on the top list of cause of death worldwide. Currently, the need for large diameter vascular graft are well-addressed by Dacron® and ePTFE synthetic graft. However, small diameter artificial vascular grafts remain an unmet clinical need. The advancement of vascular tissue engineering could provide a solution to artificially construct arterial prosthesis.